The Role of Ultrasonography for Assessment of Pseudotumor Cerebri Syndrome in the Emergency Department - David, Emanuele; Melita, Dario; Spinelli, Pietro; Cantisani, Vito (Journal of Pediatric Neurology, 2015)
Pseudotumor cerebri syndrome (PTCS) is a condition of still obscure etiology, characterized by elevated cerebrospinal fluid (CSF) pressure but no detectable intracranial CSF compositional anomalies or abnormalities of the brain parenchyma. This syndrome generally affects adult obese individuals, especially females, but it has been frequently described also in the pediatric population. Pediatric PTCS has been reported in association with secondary factors (e.g., medical illness, infections, endocrine disturbances, drug intoxication) that seem to augment intracranial pressure in a still unexplained way. Clinical signs and symptoms of PTCS in children include headache and papilledema at the funduscopic examination. The diagnosis of PTCS in children and adults usually involves brain imaging to exclude intracranial mass and/or vascular anomalies; the lumbar puncture is also crucial to confirming elevated CSF pressure (>250 mm H2O) and, lately, normal CSF contents at the chemical-physical examination. In recent years, ultrasonography has acquired an emerging role in the initial assessment of patient suspected to have PTCS. In fact, ocular ultrasounds allow the detection of optic disc swelling, suggestive of papilledema; additionally, ultrasonography allows the measurement of the retrobulbar optic nerve sheath diameter, which has been proposed as a noninvasive (indirect) method to assess the intracranial pressure. Ultrasound examination of the optic disc may therefore represent an important adjunct to funduscopic examination when assessing children with headache and/or visual disturbances, especially in the setting of the emergency department. We briefly discuss the application of ultrasonography in the assessment of pediatric patients with PTCS.
Keywords: idiopathic intracranial hypertension; pseudotumor cerebri; ultrasonography; optical coherence tomography; children; emergency department